2012
DOI: 10.1105/tpc.112.102517
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Efficient Electron Transport between Photosynthetic Membrane Proteins and Plastocyanin in Spinach Revealed Using Nuclear Magnetic Resonance

Abstract: In the photosynthetic light reactions of plants and cyanobacteria, plastocyanin (Pc) plays a crucial role as an electron carrier and shuttle protein between two membrane protein complexes: cytochrome b 6 f (cyt b 6 f) and photosystem I (PSI). The rapid turnover of Pc between cyt b 6 f and PSI enables the efficient use of light energy. In the Pc-cyt b 6 f and Pc-PSI electron transfer complexes, the electron transfer reactions are accomplished within <10 24 s. However, the mechanisms enabling the rapid associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 102 publications
1
23
0
Order By: Relevance
“…Mutational analyses in Pc from spinach have revealed that the hydrophobic residues surrounding the Cu 2+ /Cu + ion, such as Leu12 and Ala90 and the acidic residues located adjacent to the hydrophobic patch, such as Asp42, Glu43, Asp44, Glu45, Glu59, Glu60, and Asp61 are important for Pc-PSI electron transport in eukaryotic plants [39][40][41][42][43][44] and Pc-cyt b 6 f. 32,40,45,46 The hydrophobic patch residues of Pc are in close proximity to PSI and cyt b 6 f complex, whereas the acidic patch residues of Pc do not form stable salt bridges with either PSI or cyt b 6 f complex, in the electron transfer complexes. 47 The transient characteristics of the interactions on the acidic patch facilitate the rapid association and dissociation of Pc.…”
Section: Coppermentioning
confidence: 99%
“…Mutational analyses in Pc from spinach have revealed that the hydrophobic residues surrounding the Cu 2+ /Cu + ion, such as Leu12 and Ala90 and the acidic residues located adjacent to the hydrophobic patch, such as Asp42, Glu43, Asp44, Glu45, Glu59, Glu60, and Asp61 are important for Pc-PSI electron transport in eukaryotic plants [39][40][41][42][43][44] and Pc-cyt b 6 f. 32,40,45,46 The hydrophobic patch residues of Pc are in close proximity to PSI and cyt b 6 f complex, whereas the acidic patch residues of Pc do not form stable salt bridges with either PSI or cyt b 6 f complex, in the electron transfer complexes. 47 The transient characteristics of the interactions on the acidic patch facilitate the rapid association and dissociation of Pc.…”
Section: Coppermentioning
confidence: 99%
“…An NMR study of the complex between cytochrome f and plastocyanin from the cyanobacterium Nostoc showed that the binding interface involves hydrophobic residues with charged residues at the edge (Díaz-Moreno et al, 2005). A more recent NMR study of the Pc-cytb 6 f interaction using spinach components, including SG membranes, showed that there is an initial, loose electrostatic interaction and the subsequent formation of an electron transfer complex relies on hydrophobic interactions (Ueda et al, 2012).…”
Section: Affinity-mapping Afm Using Pc-functionalized Afm Probes Allomentioning
confidence: 99%
“…56 This method has been applied to identify the precise binding interface between a chemokine and the GPCR CXCR4 or plastocyanin and photosynthetic membrane proteins and provides mechanistic insight into these respective interactions. 5758 More traditional NMR chemical shift perturbation and resonance line-broadening approaches have been employed to detect the interaction of arrestin with rhodopsin. 59 Since ssNMR methods have no principle limitations on size, both protein partners can be directly observed by exploring creative isotope labeling strategies in combination with specific ssNMR pulse schemes.…”
Section: Functional Studiesmentioning
confidence: 99%